58.3k views
6 votes
.
Simplify the expression below
4(2x+8y+9)-3x+40
plz help

2 Answers

6 votes
4(2x + 8y + 9) -3x + 40
= 8x + 32y + 36 - 3x + 40
= 8x - 3x + 32y + 36 + 40
= 5x + 32y + 76
So, in conclusion, the expression: 4(2x + 8y + 9) -3x + 40 simplified is: 5x + 32y + 76.
User NewBike
by
4.4k points
1 vote

Answer:

5x+32y+76

Explanation:

First, distribute.

4 x 2x = 8x

4 x 8y = 32y

4 x 9 = 36

Then, combine like terms.

8x - 3x = 5x

36 + 40 = 76

And that leaves 5x+32y+76

User Pscuderi
by
4.4k points